Fairness and Contract Design - Fehr, Ernst; Klein, Alexander; Schmidt, Klaus M (Econometrica, 2007)
We show experimentally that fairness concerns may have a decisive impact on the actual and optimal choice of contracts in a moral hazard context. Bonus contracts that offer a voluntary and unenforceable bonus for satisfactory performance provide powerful incentives and are superior to explicit incentive contracts when there are some fair-minded players, but trust contracts that pay a generous wage up front are less efficient than incentive contracts. The principals understand this and predominantly choose the bonus contracts. These results are consistent with recently developed theories of fairness, which offer important new insights into the interaction of contract choices, fairness, and incentives.